Home Blood Pressure Monitoring: Nurses’ Role for Hypertension Control Management in Patients’ Receiving Antihypertensive Medication - Srithumsuk, Werayuth; Thummapol, Onouma (Journal of The Royal Thai Army Nurses, 2020)
This academic paper aims to review the available literature and guidelines regarding role of nurses in home blood pressure monitoring (HBPM) for the management of hypertension. HBPM plays an important role in the control and management of hypertension by offering more convenient means than an ambulatory blood pressure monitoring and being cost-effective. HBPM can aid in the diagnosis of white-coat hypertension and masked hypertension, as well as prediction of risks for cardiovascular diseases, stroke, and end stage renal disease. Generally, the measurement of home blood pressure will take place twice daily, ideally in the morning and evening. For each blood pressure recording, two consecutive measurements with at least 1-minute interval are recommended. It has been found that an upper-arm blood pressure measurement is the most widely used and have produced more accurate readings. The HBPM average of the SBP ≥ 135 mm Hg and/or DBP ≥ 85 mm Hg, is considered abnormal. Nurses play a critical role in educating patients about hypertension and its consequences, the importance of HBPM, and the necessary self-monitoring skills that include selecting an appropriate home blood pressure monitor, preparing and monitoring blood pressure, recording the results, and caring for a monitor. Therefore, it is imperative for nurses to possess a holistic and comprehensive knowledge in order to give advice and effectively care for patients. This demonstrates the quality of nursing care and affects the quality of life of patients, contributing to the reduction of disability rates and death associated with high blood pressure.